Strategi Pengembangan Potensi Wisata Desa Bukit Telago Dalam Perspektif Community Based Tourism - Juardi Juardi; Deni Handani; Sukarni Novita Sari (Institut Ilmu Sosial dan Manajemen STIAMI, 2020)
The purpose of this research is to determine the extent of community involvement at the village of Bukit Telago and how the strategy of developing tourism at the village of Bukit Telago. Descriptive qualitative is the methodology used in this study. With 30 samples consisting of officials, community and local entrepreneurs, the method of sampling is use purposive sampling and random sampling methods. The results are that community involvement at Bukit Telago tourism was only in communities around the village and the development strategy used involves three pillars namely village, community and local businessmen who are mutually integrated.